The influence of improved soil zone on liquefaction response - Demir, S.; Ozener, P.; Aydin, C. (CRC PRESS-BALKEMA, 2019)
In this study, the effect of improved soil zone on the liquefaction response is investigated through a series of numerical analyses performed by Deepsoil and OpenSees. For this purpose, a hypothetical improved liquefiable soil site with varying improvement depths is created and the effect of thickness of the overlying improved soil zone on liquefaction response is analyzed by evaluating the peak ground acceleration, max. horizontal displacement, shear strain and factor of safety against liquefaction with depth. As a result of the performed analyses, it is seen that the existence of an improved soil zone above the liquefiable soil layer does not influence the liquefaction response of the underlying liquefiable soil layer. The overall analysis results revealed that the improved soil crust and underlying liquefiable soil layer behaves separately because of the rigidity difference and the earthquake motion's characteristic has an essential impact on damage assessment.
Keywords: Geochemistry & Geophysics; Engineering